1994
DOI: 10.1161/01.cir.89.6.2736
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for induction of intracellular adhesion molecule-1 in the viable border zone associated with ischemia-reperfusion injury of the dog heart.

Abstract: BACKGROUND Acute inflammation may play a role in injury during reperfusion following myocardial ischemia. Studies in vitro suggest that intracellular adhesion molecule-1 (ICAM-1) mediates neutrophil adherence to cardiac myocytes and neutrophil-mediated injury. We have shown cytokine activity in postischemic cardiac lymph sufficient to maximally express ICAM-1 on myocytes and that ICAM-1 mRNA is found in the previously ischemic myocardium early in reperfusion. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…However, when administered 30 minutes after established coronary microembolization, methylprednisolone no longer prevented leukocyte infiltration, possibly because initial steps of leukocyte activation and leukocyte/endothelium interaction had already occurred. 31,35,36 Glucocorticoids have previously been shown to inhibit the expression of TNF-␣ mRNA in immunologically activated rat peritoneal mast cells, 16 to suppress the production of TNF-␣ in serum and myocardium of lipopolysaccharidestimulated rats, 17 and to abolish the release of TNF-␣ into serum of humans during cardiac surgery. 15 Glucocorticoids also attenuate the infiltration of TNF-␣-producing macrophages/monocytes after coronary microembolization in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…However, when administered 30 minutes after established coronary microembolization, methylprednisolone no longer prevented leukocyte infiltration, possibly because initial steps of leukocyte activation and leukocyte/endothelium interaction had already occurred. 31,35,36 Glucocorticoids have previously been shown to inhibit the expression of TNF-␣ mRNA in immunologically activated rat peritoneal mast cells, 16 to suppress the production of TNF-␣ in serum and myocardium of lipopolysaccharidestimulated rats, 17 and to abolish the release of TNF-␣ into serum of humans during cardiac surgery. 15 Glucocorticoids also attenuate the infiltration of TNF-␣-producing macrophages/monocytes after coronary microembolization in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically, it has been shown that neutrophils first penetrate the infarcted myocardium, followed by macrophages, and it has been reported that neutrophils are associated with reperfusion injury, in concert with the induction of intracellular adhesion molecule-1 (ICAM-1), interleukin (IL)-6, or IL-8 (Hawkins et al, 1996;Kukielka et al, 1993Kukielka et al, , 1995aKukielka et al, , 1995bNeumann et al, 1995;Youker et al, 1994). It has also been reported that reperfusion is associated with an increase in the number of macrophages compared with the nonreperfused Mean number of macrophages in the hearts at 1 hour, 3 hours, and 6 hours after reperfusion (R).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the reperfusion period, the heart was stopped by infusion of saturated potassium chloride and removed immediately and processed for RNA isolation or immunohistochemistry and in situ hybridization as previously described. 20,22 Adjacent sections were used for blood flow determination with radiolabeled microspheres as previously described. 26,27 Analysis of RNA, blood flow determination, and histopathology were performed independently in different laboratories and in a blinded fashion.…”
Section: Ischemia-reperfusion Protocolsmentioning
confidence: 99%
“…20 Digoxigenin-labeled probes were prepared by in vitro transcription from a linearized template with the Genius RNA probe labeling kit (Boehringer Mannheim Corp) according to the manufacturer's instructions. A 215-bp [bases 483 to 697 of the published sequence 22 ] fragment of canine IL-6 cDNA was obtained with polymerase chain reaction amplification and was subcloned into the polymerase chain reaction plasmid (Invitrogen) so that the use of SP6 polymerase would result in the generation of single-stranded antisense (3Ј-5Ј) and the use of T7 polymerase would result in the generation of the sense (5Ј-3Ј) probe.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation